Dental Practice Management - An Overview - Dr Viswapurna Senguttuvan; Dr Thillaikkarasi Viswapurna (International Journal of Medical Toxicology and Legal Medicine, 2024)
Dental practice management includes an extensive spectrum of duties, which includes optimizing patient satisfaction, adherence to healthcare guidelines, in addition to efficient personnel management and scheduling periodic dental appointments. Enhanced experiences for patients and pleasant working conditions for staff are two essentials of a well-managed and ordered practice, which can help lower employee turnover and boost overall productivity. In order to optimize output, effective practice management additionally demands integrating contemporary technologies into their daily operations. This research aims to provide an overview of the elements that contribute to successful dental practice management.